Correlation Between Perceived Social Support and Self Efficacy in Final Students Who Are Preparing Thesis - Mila Rahmawati; Imammul Insan (Formosa Journal of Social Sciences (FJSS), 2024)
This research aims to determine the relationship between perceived social support and self-efficacy in final students who are writing their thesis. This research uses a quantitative research approach with a descriptive type of research. The sampling technique for this research uses a purposive sampling technique with students being the research sample consisting of 203 students using the Krejcie table. Test construct validity by looking at the total item correlation coefficient equal to or greater than 0.138. The instrument reliability test uses Cronbach's alpha value, namely 0.8. The results of this study indicate that there is a positive and significant correlation between Perceived social support and self-efficacy with a correlation value (rxy) of 0.492 with a calculated p value = 0.0001 / P < 0.05